2006
DOI: 10.1007/s10495-006-9788-2
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ is a key target of butyrate-induced caspase-3 activation in the colorectal cancer cell line Caco-2

Abstract: Our data clearly unveil PPARgamma as a key target in the butyrate-induced signalling cascade leading to apoptosis via caspase-3 in Caco-2 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…It is tempting to propose that RS-75 and inulin supplementation modulated the Treg compartment by causing changes in the gut's microbial ecology, resulting in increased butyrate levels that subsequently activate PPAR g (41). Although there was no direct correlation between improved lesions due to dietary fiber and inflammatory markers, clinically effective fibers induced immunoregulation, as exemplified by upregulated SOCS3 by SCF, upregulated PPARg by SCF and RS-75, increased Treg by RS-75 and inulin, and suppressed PP-derived IFNg by SCF, RS-75, and inulin.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to propose that RS-75 and inulin supplementation modulated the Treg compartment by causing changes in the gut's microbial ecology, resulting in increased butyrate levels that subsequently activate PPAR g (41). Although there was no direct correlation between improved lesions due to dietary fiber and inflammatory markers, clinically effective fibers induced immunoregulation, as exemplified by upregulated SOCS3 by SCF, upregulated PPARg by SCF and RS-75, increased Treg by RS-75 and inulin, and suppressed PP-derived IFNg by SCF, RS-75, and inulin.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate has the capacity to modulate histone acetylation by acting as a potent inhibitor of histone deacetylases (HDACs) and thereby modifies transcriptional activity of several genes. Described effects of butyrate include the downregulation of cyclin D1 (CCND1) [Lallemand et al, 1996], the induction of the inhibitor of cyclin-dependant kinases p21 WAF1/Cip1 (CDKN1A) [Nakano et al, 1997] and the peroxisome proliferator activated receptor gamma (PPARg) [Schwab et al, 2006] finally leading to the blockage of the cell cycle and the induction of apoptosis in colon cancer cells. The mediators of this effect are still poorly characterized, but in recent years, several genes have been identified, which are regulated in a butyrate-dependent manner.…”
mentioning
confidence: 99%
“…7 It has recently been shown that 1 mM NaB is the best working concentration to activate the differentiation program in CRCs without triggering apoptosis, whereas 5 mM NaB is sufficient to induce a p53-independent apoptotic cell death by activating a pathway involving p38, PPARg and caspases. 6,8 Several intracellular signaling cascades have been implicated in the regulation of the proliferation-differentiation balance in enterocytes by the coordinated expression of the genome in response to environmental cues. During enterocyte differentiation of CRCs the ERK pathway is switched off, whereas PI 3 K class I and p38 activities are increased and essential for full differentiation.…”
mentioning
confidence: 99%